Slit2-Mediated Metabolic Reprogramming in Bone Marrow-Derived Macrophages Enhances Antitumor Immunity - Kaul, Kirti; Benej, Martin; Mishra, Sanjay; Ahirwar, Dinesh K.; Yadav, Marshleen; Stanford, Kristin I.; Jacob, Naduparambil K.; Denko, Nicholas C.; Ganju, Ramesh K. (Frontiers in Immunology, 2021)
Slit2 exerts anti-tumor effects in various cancers, however the underlying mechanism, especially its role in regulating the immune system is unknown. Elucidating the behavior of macrophages in tumor progression can potentially improve immunotherapy. Using a spontaneous Mammary Tumor Virus promoter-polyoma middleT antigen (PyMT) breast cancer mouse model, we observed that Slit2 increased the abundance of anti-tumor M1 macrophage in the bone marrow. Moreover, myeloablated PyMT mice injected with Slit2 treated bone marrow allografts showed a marked reduction in tumor growth, with enhanced recuitment of M1 in their tumor stroma. Mechanistic studies revealed that Slit2 significantly enhanced glycolysis and reduced fatty acid oxidation in bone marrow derived macrophages (BMDMs). Slit2 treatment also altered mitochondrial respiration metabolites in macrophages isolated from healthy human blood that were treated with plasma from breast cancer patients. Overall, this study, for the first time, shows that Slit2 increases BMDM polarization towards anti-tumor phenotype by modulating immune-metabolism. Furthermore, this study provides evidence that soluble Slit2 could be developed as novel therapeutic strategy to enhance anti-tumor immune response.